Cashless Society Sebagai Pemoderasi Pengaruh Fintech Payment Gateway Terhadap Kinerja Keuangan UMKM di Kota Denpasar - Ketut Tanti Kustina; Wahyu Santoso Aji (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2023)
The MSME sector impotant a strategic role in supporting the national economy by absorbing labor and sharing development outcomes. In the development of the MSME sector,  the Covid-19 pandemic has affected the resilience and sustainability of SMEs. Entrepreneurs are driven to the ability to innovate using the sophistication of technology in their business.The purpose of this research is to identify the influence of variables fintech payment gateway on the financial performance of MSMEs in Denpasar City and identify variables cashless society moderate the influence between fintech payment gateway on the financial performance of MSMEs in Denpasar City. The population using MSMEs in the culinary field in Denpasar City is 9.679 business units. Determining the sample using purposive sampling and determining the number of samples using the solvin formula yields 99 respondents. Research material was collected by distributing questionnaires through google forms. The data analysis technique of this study uses simple regression analysis and MRA using SPSS. The research results show that 1) the variable payment gateway has a positive and significant effect on the financial performance of small and medium enterprises in the city of Denpasar. 2) variables cashless society that can moderated strengthen the effect of payment gateway on the financial performance of SMEs in Denpasar city. Keywords: Fintech Payment Gateway, Financial Performance of MSME, Cashless Society